PERSONALITY TYPE AND WORK FAMILY CONFLICT IN FEMALE DOCTORS - Gulzar, Mehreen; Khalid, Shazia (Pakistan Armed Forces Medical Journal, 2016)
Objective: To assess the association between personality types and work-family conflict among female doctors. Moreover it was aimed that which personality type is more experience work-family conflict in female doctors. Study Design: Cross sectional study design. Place and Duration of Study: Study was conducted in Institute of Applied Psychology Lahore Pakistan from Dec 2012 to Jun 2013. Material and Methods: The sample comprised of 154 female doctors selected from three teaching hospitals of Lahore. The age range of female doctors was 25 years to 45 years (M= 30.56 ± 5.96). Type A/B behavior pattern scale and work-family conflict scale were used to assess variables. Results: Correlation analysis showed that there was a significant positive relationship between personality type A and work inference with family plus family inference with work in female doctors. Linear Regression analysis revealed that personality type A emerged as a significant predictor of work inference to family and family inference to work. Conclusion: The present research emphasizes the significance for medical doctor’s organization and career guidance. Being adapting behaviors of type B personality, they experience less work family conflict and work for the betterment of society as well as personal self.